A Grism Design Review and the As-Built Performance of the Silicon Grisms for JWST-NIRCam. (9th May 2017) - Deen, Casey P.; Gully-Santiago, Michael; Wang, Weisong; Pozderac, Jasmina; Mar, Douglas J.; Jaffe, Daniel T.
Abstract: Grisms are dispersive transmission optics that find their most frequent use in instruments that combine imaging and spectroscopy. This application is particularly popular in the infrared where imagers frequently have a cold pupil in their optical path that is a suitable location for a dispersive element. In particular, several recent and planned space experiments make use of grisms in slit-less spectrographs capable of multi-object spectroscopy. We present an astronomer-oriented general purpose introduction to grisms and their use in current and future astronomical instruments. We present a simple, step-by-step procedure for adding a grism spectroscopy capability to an existing imager design. This procedure serves as an introduction to a discussion of the device performance requirements for grisms, focusing in particular on the problems of lithographically patterned silicon devices, the most effective grism technology for the 1.1–8 micron range. We begin by summarizing the manufacturing process of monolithic silicon gratings. We follow this with a report in detail on the as-built performance of parts constructed for a significant new space application, the NIRCam instrument on James Webb Space Telescope and compare these measurements to the requirements.